An inductor and a method of manufacturing the same
Patent Information
- Application Number
- CN202611339764.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-30
AI Technical Summary
低熔点氧化物在烧结过程中形成液相,加速物质迁移和致密化,但液相冷却后往往在晶界处形成非磁性或弱磁性玻璃相,这些玻璃相的存在会降低磁导率、增加畴壁钉扎,导致矫顽力增大、损耗升高
本发明以锰锌铁氧体为核体,可以为芯体提供优异的磁化能力和储能密度;以锂锌铁氧体为壳体,利用其高电阻率和低高频损耗的特点,抑制高频下涡流的产生和传播。核体与壳体的功能分工使得芯体在低频下具有较高的磁导率和饱和磁通密度,在高频下又具有较低的损耗,从而实现宽频范围内优异的综合磁性能。
Smart Images

Figure REF-OBJ-1788226535888-000001
Abstract
Description
Technical Field
[0001] This invention relates to the field of inductor technology, specifically to an inductor and its fabrication method. Background Technology
[0002] As a fundamental passive electronic component, inductors play crucial roles in electronic circuits, including energy storage, filtering, oscillation, delay, notch filtering, and signal coupling. With the rapid development of power electronics, communication, new energy, and the electric vehicle industry, electronic devices are constantly evolving towards higher frequencies, smaller sizes, greater integration, higher efficiency, and higher reliability, placing increasingly stringent demands on inductor performance. In particular, power inductors in switching power supplies and power converters have seen their operating frequencies increase from tens of kilohertz to hundreds of kilohertz or even megahertz, while simultaneously requiring inductors to possess low DC resistance, high saturation current, small size, and good electromagnetic compatibility characteristics.
[0003] One of the core components determining inductor performance is its soft magnetic core. The choice of soft magnetic core material and its fabrication process directly affect the inductor's inductance, quality factor, losses, temperature stability, saturation characteristics, and reliability. Manganese-zinc ferrite is an important class of soft magnetic ferrites, widely used in switching power supply transformers and filter inductors. However, manganese-zinc ferrite has relatively low resistivity. As the operating frequency increases, induced eddy currents flow along the grain interior and grain boundaries within the core, generating Joule heat losses. Simultaneously, residual losses caused by domain wall resonance and natural resonance also increase sharply, leading to a decrease in permeability and limiting its application in high-frequency bands. Lithium-zinc ferrite, on the other hand, has higher resistivity. To combine the advantages of both manganese-zinc ferrite and lithium-zinc ferrite, researchers have attempted to combine them. Common composite methods include physical mixing, mechanical ball milling, and layered sintering. However, simple physical mixing or mechanical composites often fail to form a uniform microstructure and good interfacial bonding. Besides the inherent problems of ferrite materials, soft magnetic ferrite cores typically require the addition of sintering aids during molding and sintering to lower the sintering temperature, promote densification, improve microstructure, and enhance mechanical strength. Commonly used sintering aids include low-melting-point oxides such as bismuth oxide and vanadium oxide, as well as alkaline earth metal compounds such as calcium carbonate, strontium carbonate, and barium carbonate. Low-melting-point oxides form a liquid phase during sintering, accelerating material migration and densification. However, after cooling, the liquid phase often forms non-magnetic or weakly magnetic glassy phases at grain boundaries. The presence of these glassy phases reduces permeability, increases domain wall pinning, leading to increased coercivity and losses. While alkaline earth metal compounds can promote uniform grain growth, their effect on improving grain boundary resistivity is limited, making it difficult to effectively suppress high-frequency eddy current losses. Furthermore, a single aid often cannot simultaneously meet the requirements of low-temperature sintering, high density, high resistivity grain boundaries, and good magnetic properties. Therefore, developing a multi-component sintering aid system with synergistic effects is of great significance for improving the overall performance of soft magnetic ferrite cores.
[0004] To address the aforementioned problems, this invention proposes an inductor and its fabrication method. By constructing a composite structure with manganese-zinc ferrite as the core, lithium-zinc ferrite as the shell, and a titanium-manganese-zinc-lithium ferrite transition layer between the core and shell, synergistic optimization of magnetic properties and high-frequency performance is achieved. Simultaneously, a ternary sintering aid composed of calcium carbonate, tantalum oxide, and tin dioxide is employed to further improve the core's densification, microstructure, and overall magnetic properties through multiple mechanisms, including liquid-phase sintering, high grain boundary resistivity, and grain refinement. Summary of the Invention
[0005] Purpose of the invention: To address the above-mentioned technical problems, this invention proposes an inductor and its fabrication method.
[0006] The technical solution adopted is as follows: An inductor includes a soft magnetic core, said soft magnetic core being made of a core-shell structured composite ferrite and a sintering aid; The core-shell composite ferrite includes a manganese-zinc ferrite core, a titanium-manganese-zinc-lithium ferrite transition layer, and a lithium-zinc ferrite shell.
[0007] Furthermore, the chemical structural formula of the manganese-zinc ferrite core is: Mn 1-x Zn x Fe2O4, 0.25≤x≤0.45.
[0008] Furthermore, the chemical structural formula of the titanium-manganese-zinc-lithium ferrite transition layer is: Li y Zn 0.9-y- z Mn z Ti 0.2 Fe 1.9 O4, 0.2≤y≤0.4, 0.05≤z≤0.15.
[0009] Furthermore, the chemical structural formula of the lithium-zinc ferrite shell is: Li 0.5-0.5q Zn q Fe 2.5-0.5q O4, 0.2≤q≤0.4.
[0010] Furthermore, the sintering aid is composed of calcium carbonate, tantalum oxide, and tin dioxide.
[0011] Furthermore, the mass ratio of calcium carbonate, tantalum oxide, and tin dioxide is 1-3:1-3:1-3.
[0012] Furthermore, the mass ratio of the core-shell composite ferrite to the sintering aid is 1:1%-5%.
[0013] Furthermore, the method for preparing the soft magnetic core is as follows: The core-shell composite ferrite is mixed with the sintering aid, a binder is added to granulate the mixture, and it is pressed into a blank; the blank is then sintered to obtain the soft magnetic core.
[0014] Furthermore, the preparation method of the core-shell structured composite ferrite is as follows: Manganese, zinc, and iron sources were weighed, dissolved in water, and then a manganese-zinc ferrite core precursor was prepared by boiling reflux co-precipitation. The manganese-zinc ferrite core precursor was pre-calcined at 600-700℃, then dispersed in a solution containing lithium, manganese, zinc, titanium, iron, and urea. The mixture was sealed and reacted at 110-130℃ for 12-48 hours, then allowed to stand for aging for another 12-48 hours. The precipitate was collected, washed, and dried, and then dispersed again in a solution containing lithium, zinc, iron, and urea. The mixture was sealed and reacted at 110-130℃ for 12-48 hours, then allowed to stand for aging for another 12-48 hours. The precipitate was collected, washed, and dried to obtain the final product.
[0015] Furthermore, the sintering temperature is 1150-1250℃.
[0016] Furthermore, the sintering holding time is 2-6 hours.
[0017] Furthermore, both the pre-burning atmosphere and the sintering atmosphere are argon.
[0018] The present invention also provides an inductor comprising the aforementioned soft magnetic core. The inductor includes a soft magnetic core base, a flat coil, and a metal powder coating layer. The soft magnetic core base is made of the aforementioned core-shell composite ferrite and sintering aid, employing a T-shaped structure to provide a winding platform for the coil. The flat coil is mounted on the winding posts of the soft magnetic core, and the leads at both ends of the coil are bent and directly used as electrode pins. The entire inductor is coated with metal powder at room temperature and then hot-pressed and cured to form a single integrated structure.
[0019] In the fabrication process, a flat coil is first positioned and mounted on a soft magnetic core. The coil can be made of flat wire with a diameter and thickness of 0.03-0.6 mm, with 5-30 turns, and can be designed as a multi-layer stacked or spiral wound structure. In terms of coil arrangement, differential-mode suppression of 8-30 dB can be achieved through differential-mode flux cancellation, or common-mode filtering of 15-50 dB can be achieved through common-mode flux superposition. Subsequently, metallic magnetic powder with a particle size range of 10-200 μm is filled around the coil and core. The magnetic powder material can be the same as the soft magnetic core matrix, or different magnetic materials can be selected according to application requirements. After filling, the entire unit is placed in a mold and thermo-pressed and cured under conditions of 0.8-1.5 T per cavity, temperature 180±10℃, and holding time 40-60 s to obtain a one-piece molded inductor.
[0020] In this inductor structure, the flat coil has a high conductor fill rate, which can significantly reduce DC resistance and conduction loss; the two ends of the coil are directly bent to form electrode leads, eliminating the need for soldering and avoiding hidden wire breaks caused by solder stress and bent leads; the metal magnetic powder tightly coats the coil and soft magnetic core, forming multi-directional heat dissipation channels, which is conducive to rapid heat conduction and diffusion and reduces temperature rise; at the same time, the magnetic circuit is continuous without concentrated air gaps, and the magnetic field is uniformly distributed, effectively avoiding local magnetic saturation and improving saturation current and performance stability.
[0021] Through the synergistic combination of the soft magnetic core, flat coil, and metal magnetic powder coating, the inductor of this invention achieves low DC resistance, high saturation current, high reliability, and good heat dissipation performance while maintaining excellent magnetic properties. It is particularly suitable for the field of high-frequency, high-current, and miniaturized power inductors.
[0022] Compared with the prior art, the present invention has the following beneficial effects: This invention uses manganese-zinc ferrite as the core, which provides excellent magnetization and energy storage density; and lithium-zinc ferrite as the shell, utilizing its high resistivity and low high-frequency loss to suppress the generation and propagation of eddy currents at high frequencies. This functional division between the core and shell allows the core to possess high permeability and saturation flux density at low frequencies, while exhibiting low losses at high frequencies, thus achieving excellent overall magnetic performance over a wide frequency range.
[0023] While core-shell structures enable functional division, direct contact between the core and shell can easily lead to stress concentration at the interface due to differences in lattice constants, coefficients of thermal expansion, and sintering shrinkage characteristics. This can result in microcracks, porosity, and even phase separation, leading to decreased permeability and increased losses. This invention incorporates a titanium-manganese-zinc-lithium ferrite transition layer between the core and shell. This layer contains the main constituent elements of both the core and shell, and additionally introduces titanium ions. Its lattice constant and coefficient of thermal expansion are well-matched to both the core and shell, effectively buffering interface stress, preventing interface defects, and improving the bonding strength and structural integrity of the core-shell interface. Furthermore, the introduction of titanium ions alters the magnetocrystalline anisotropy constant and magnetostriction coefficient of the ferrite. A decrease in the magnetostriction coefficient helps reduce stress losses caused by lattice distortion during magnetization; appropriate adjustment of the magnetocrystalline anisotropy constant facilitates reversible domain wall movement, reducing domain wall resonance losses and residual losses. Therefore, the transition layer not only improves the interface bonding, but also further reduces high-frequency losses from the perspective of intrinsic magnetic properties.
[0024] This invention employs a ternary sintering aid system composed of calcium carbonate, tantalum oxide, and tin dioxide, with a significant synergistic effect among the three components. Calcium carbonate decomposes at high temperatures to produce calcium oxide and carbon dioxide. Calcium oxide can form a low-melting-point phase with certain components in the ferrite, generating a suitable amount of liquid phase during sintering, promoting particle rearrangement and mass migration, accelerating the densification process, and lowering the sintering temperature. Tantalum oxide is a high-melting-point, high-resistivity oxide. During sintering, tantalum oxide mainly accumulates at grain boundaries, forming a high-resistivity grain boundary phase or segregation layer. This high-resistivity grain boundary effectively hinders electron conduction between grains, significantly increasing the overall resistivity of the material, thereby reducing eddy current losses at high frequencies. Simultaneously, the pinning effect of tantalum oxide at grain boundaries inhibits grain migration, prevents abnormal grain growth, and results in uniform and refined grain size. Uniform and fine grains are beneficial for improving the mechanical strength and frequency stability of the material. Tin dioxide also possesses high resistivity and chemical stability. The presence of tin dioxide at grain boundaries can further modify the grain boundary structure, forming a continuous high-resistivity grain boundary network in synergy with tantalum oxide. Furthermore, tin dioxide can undergo a solid-state reaction with some ferrite components at high temperatures to generate composite oxides with high resistivity, enhancing the insulation and thermal stability of the grain boundaries. When these three components are used together, multiple mechanisms, such as liquid-phase sintering, high grain boundary resistivity enhancement, and grain refinement, work synergistically, enabling soft magnetic cores to achieve high-density, uniform microstructure, high-resistivity grain boundaries, and excellent overall magnetic properties at relatively low sintering temperatures.
[0025] Through the synergistic effect of the aforementioned multiple mechanisms, the soft magnetic core of this invention exhibits significant advantages in initial permeability, saturation flux density, high-frequency loss, and temperature stability. The overall performance is significantly improved, making it particularly suitable for high-frequency, high-current, and miniaturized power inductors. In summary, this invention, through the synergistic effect of core-shell structure design, the introduction of a transition layer, and ternary sintering aids, effectively improves the problems of high high-frequency loss, poor temperature stability, poor interface bonding, and the difficulty in simultaneously achieving densification and high resistivity in existing soft magnetic ferrite cores. It provides a soft magnetic core, inductor, and its fabrication method that features high-frequency low loss, high permeability, and high saturation flux density, possessing broad application prospects and industrialization value. Detailed Implementation
[0026] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Techniques not mentioned in this invention refer to existing technologies. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0027] Example 1: A method for preparing a soft magnetic core: According to Mn 0.65 Zn0.35 Manganese sulfate, zinc sulfate, and ferric nitrate were weighed out in stoichiometric proportions for Fe₂O₄ and dissolved in deionized water to prepare a mixed solution of 500 mL with a total metal ion concentration of 0.5 mol / L. Under stirring, the mixed solution was heated to boiling while ammonia was slowly added dropwise to maintain the pH of the reaction system at 10⁻¹¹. The reaction was continued under boiling reflux for 5 h. After the reaction was complete, the resulting precipitate was repeatedly washed with deionized water and anhydrous ethanol until the filtrate was neutral. It was then dried at 80 °C for 12 h to obtain the manganese-zinc ferrite core precursor. The precursor was pre-calcined at 650 °C under argon protection for 2 h to obtain the manganese-zinc ferrite core.
[0028] According to Li 0.3 Zn 0.5 Mn 0.1 Ti 0.2 Fe 1.9 In O4, lithium nitrate, zinc nitrate, manganese nitrate, titanium sulfate, and ferric nitrate were weighed and dissolved in deionized water to prepare 100 mL of a mixed solution with a total metal ion concentration of 0.5 mol / L. Urea was then added (the ratio of urea to the total molar amount of metal ions was 5:1). The above manganese-zinc ferrite core was dispersed in the above solution, sealed, and reacted at 120°C for 24 h, followed by aging at rest for 24 h. The precipitate was collected, washed, and dried to obtain the core coated with a transition layer.
[0029] According to Li 0.35 Zn 0.3 Fe 2.35 Lithium nitrate, zinc nitrate, and ferric nitrate were weighed out in deionized water according to the stoichiometric ratio of O4 to prepare a mixed solution of 200 mL with a total metal ion concentration of 0.5 mol / L. Urea was added (the molar ratio of urea to the total metal ions was 5:1). The core with the transition layer was dispersed in the above solution, sealed, and reacted at 120 °C for 24 h, followed by aging at rest for 24 h. The precipitate was collected, washed, and dried to obtain a core-shell composite ferrite.
[0030] The obtained core-shell composite ferrite was mixed with sintering aids (calcium carbonate, tantalum oxide, and tin dioxide in a mass ratio of 1:1:1) at a mass ratio of 1:1%, and ball-milled for 4 hours. Then, 8% (by weight of the powder) of a 5wt% polyvinyl alcohol aqueous solution was added for granulation. The granulated powder was pressed into T-shaped blanks under a pressure of 200 MPa, and then sintered at 1200℃ under argon protection for 4 hours. After furnace cooling, a soft magnetic core was obtained.
[0031] Example 2: This example is essentially the same as Example 1, except that the obtained core-shell composite ferrite is mixed with sintering aids (calcium carbonate, tantalum oxide, and tin dioxide in a mass ratio of 1:1:1) at a mass ratio of 1:2%, ball-milled for 4 hours, and then granulated by adding 8% (by weight of the powder) of a 5wt% polyvinyl alcohol aqueous solution. The granulated powder is pressed into T-shaped blanks under 200 MPa pressure, then sintered at 1200℃ under argon protection for 4 hours, and cooled in the furnace to obtain a soft magnetic core.
[0032] Example 3: This example is essentially the same as Example 1, except that the obtained core-shell composite ferrite is mixed with sintering aids (calcium carbonate, tantalum oxide, and tin dioxide in a mass ratio of 1:1:1) at a mass ratio of 1:3%, ball-milled for 4 hours, and then granulated by adding 8% (by weight of the powder) of a 5wt% polyvinyl alcohol aqueous solution. The granulated powder is pressed into T-shaped blanks under 200 MPa pressure, then sintered at 1200℃ under argon protection for 4 hours, and cooled in the furnace to obtain a soft magnetic core.
[0033] Example 4: Essentially the same as Example 1, except that the obtained core-shell composite ferrite was mixed with sintering aids (calcium carbonate, tantalum oxide, and tin dioxide in a mass ratio of 1:1:1) at a mass ratio of 1:4%, ball-milled for 4 hours, and then granulated by adding 8% (by weight of the powder) of a 5wt% polyvinyl alcohol aqueous solution. The granulated powder was pressed into T-shaped blanks under 200 MPa pressure, then sintered at 1200℃ under argon protection for 4 hours, and cooled in the furnace to obtain a soft magnetic core.
[0034] Example 5: Essentially the same as Example 1, except that the obtained core-shell composite ferrite was mixed with sintering aids (calcium carbonate, tantalum oxide, and tin dioxide in a mass ratio of 1:1:1) at a mass ratio of 1:5%, ball-milled for 4 hours, and then granulated by adding 8% (by weight of the powder) of a 5wt% polyvinyl alcohol aqueous solution. The granulated powder was pressed into T-shaped blanks under 200 MPa pressure, then sintered at 1200℃ under argon protection for 4 hours, and cooled in the furnace to obtain a soft magnetic core.
[0035] Example 6: Basically the same as Example 1, except that the sintering aid is composed of calcium carbonate, tantalum oxide and tin dioxide in a mass ratio of 3:1:1.
[0036] Example 7: Basically the same as Example 1, except that the sintering aid is composed of calcium carbonate, tantalum oxide and tin dioxide in a mass ratio of 1:3:1.
[0037] Example 8: Basically the same as Example 1, except that the sintering aid is composed of calcium carbonate, tantalum oxide and tin dioxide in a mass ratio of 1:1:3.
[0038] Comparative Example 1: The process is basically the same as in Example 1, except that a titanium-manganese-zinc-lithium ferrite transition layer is not provided. Instead, the pre-calcined manganese-zinc ferrite core is directly dispersed in the shell raw material solution for coating.
[0039] Comparative Example 2: The process is basically the same as in Example 1, except that a lithium-zinc ferrite shell is not provided. Instead, only a core body with a coating transition layer is prepared, which is then directly mixed with a sintering aid, granulated, pressed, and sintered.
[0040] Comparative Example 3: The process is basically the same as in Example 1, except that the titanium-manganese-zinc-lithium ferrite transition layer and the lithium-zinc ferrite shell are not set. That is, the prepared core is directly mixed with the sintering aid, granulated, pressed and sintered.
[0041] Comparative Example 4: It is basically the same as Example 1, except that tantalum oxide is not added to the sintering aid, and it is composed only of calcium carbonate and tin dioxide in a mass ratio of 1:1.
[0042] Comparative Example 5: It is basically the same as Example 1, except that tin dioxide is not added to the sintering aid, and it is composed only of calcium carbonate and tantalum oxide in a mass ratio of 1:1.
[0043] Comparative Example 6: It is basically the same as Example 1, except that calcium carbonate is not added to the sintering aid, and it is composed only of tin dioxide and tantalum oxide in a mass ratio of 1:1.
[0044] Performance testing The samples required for performance testing were prepared according to the methods in the examples and comparative examples, and the following performance tests were performed: Initial permeability: The inductance was measured using an impedance analyzer at a frequency of 100kHz and a magnetic flux density of 0.25mT to calculate the initial permeability.
[0045] Saturation magnetic induction intensity: A DC magnetization characteristic analyzer was used; the maximum magnetization force Hm set during the test was 1194 A / m; the number of turns of the primary and secondary coils: N1=N2=20. Test temperature range: 25-120℃, and the diameter of the silk-covered wire used for the test was 0.35mm.
[0046] Power loss: A 5-turn coil with two-color wire was used in Pe-Bm test mode, with Bm set to 200mT, frequency at 100kHz, and temperature at 25-120℃. The temperature characteristic curve of the core loss was obtained. The diameter of the insulated wire used in the test was 0.35mm. Measurements were performed using an automatic AC magnetic analyzer.
[0047] Resistivity: The resistance of the sample was tested at 25℃, 20 Hz and 5V and the resistivity was calculated.
[0048] The performance test results are shown in Table 1 below: Table 1:
[0049] In the embodiments, due to the use of a complete core-shell composite ferrite structure and the inclusion of a titanium-manganese-zinc-lithium ferrite transition layer and a lithium-zinc ferrite shell, the initial permeability is generally high, and the saturation magnetic induction intensity remains at a high level at both room temperature and high temperature. Simultaneously, the power loss is relatively low, and the resistivity is significantly improved. In particular, the embodiment with a moderate amount of sintering aid exhibits the most outstanding overall performance, demonstrating higher initial permeability, higher saturation magnetic induction intensity, and lower power loss. As the amount of aid continues to increase, although the resistivity further increases, the magnetic properties decrease somewhat, indicating that an appropriate amount of aid helps promote densification and improve the microstructure, while excessive amounts may introduce non-magnetic phases and degrade magnetic properties. When the proportion of aid varies within a reasonable range, although the performance fluctuates to some extent, it still maintains an excellent overall level, demonstrating good formulation tolerance.
[0050] In contrast, the comparative examples lacking a transition layer exhibited poorer core-shell interface bonding, resulting in decreased permeability, significantly increased losses, and decreased resistivity. The comparative examples lacking a high-resistivity shell showed decreased resistivity and increased high-frequency losses. The comparative examples retaining only a manganese-zinc ferrite core showed significantly lower permeability and saturation magnetic induction, the highest losses, and the lowest resistivity, indicating that the core-shell structure and transition layer are indispensable for performance improvement. The comparative examples lacking tantalum oxide, tin dioxide, or calcium carbonate, respectively, resulted in incomplete sintering aid systems, insufficient densification, or limited improvement in grain boundary resistance, leading to varying degrees of decrease in magnetic properties, increased losses, and lower resistivity compared to the examples.
[0051] In summary, the synergistic effect of the core-shell structure, transition layer, high resistivity shell, and ternary sintering aid is key to obtaining a soft magnetic core with high frequency, low loss, high permeability, and high saturation magnetic induction. The absence of any one of these components will lead to a significant deterioration in overall performance.
[0052] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An inductor, characterized in that, Includes a soft magnetic core, which is made of a core-shell structured composite ferrite and a sintering aid; The core-shell composite ferrite includes a manganese-zinc ferrite core, a titanium-manganese-zinc-lithium ferrite transition layer, and a lithium-zinc ferrite shell.
2. The inductor as described in claim 1, characterized in that, The chemical structural formula of the manganese-zinc ferrite core is: Mn 1-x Zn x Fe2O4, 0.25≤x≤0.
45.
3. The inductor as described in claim 1, characterized in that, The chemical structural formula of the titanium-manganese-zinc-lithium ferrite transition layer is: Li y Zn 0.9-y-z Mn z Ti 0.2 Fe 1.9 O4, 0.2≤y≤0.4, 0.05≤z≤0.
15.
4. The inductor as described in claim 1, characterized in that, The chemical structural formula of the lithium-zinc ferrite shell is: Li 0.5-0.5q Zn q Fe 2.5-0.5q O4, 0.2≤q≤0.
4.
5. The inductor as described in claim 1, characterized in that, The sintering aid consists of calcium carbonate, tantalum oxide, and tin dioxide.
6. The inductor as described in claim 5, characterized in that, The mass ratio of calcium carbonate, tantalum oxide, and tin dioxide is 1-3:1-3:1-3.
7. The inductor as claimed in claim 1, characterized in that, The mass ratio of the core-shell composite ferrite to the sintering aid is 1:1%-5%.
8. The inductor as claimed in claim 1, characterized in that, The soft magnetic core is prepared as follows: The core-shell composite ferrite is mixed with the sintering aid, a binder is added to granulate the mixture, and it is pressed into a green body. The green body is then sintered at 1150-1250℃ to obtain the soft magnetic core.
9. The inductor as claimed in claim 8, characterized in that, The preparation method of the core-shell structured composite ferrite is as follows: Manganese, zinc, and iron sources were weighed, dissolved in water, and then a manganese-zinc ferrite core precursor was prepared by boiling reflux co-precipitation. The manganese-zinc ferrite core precursor was pre-calcined at 600-700℃, then dispersed in a solution containing lithium, manganese, zinc, titanium, iron, and urea. The mixture was sealed and reacted at 110-130℃ for 12-48 hours, then allowed to stand for aging for another 12-48 hours. The precipitate was collected, washed, and dried, and then dispersed again in a solution containing lithium, zinc, iron, and urea. The mixture was sealed and reacted at 110-130℃ for 12-48 hours, then allowed to stand for aging for another 12-48 hours. The precipitate was collected, washed, and dried to obtain the final product.
10. A method for manufacturing an inductor, wherein the inductor is the inductor according to any one of claims 1-9, characterized in that, The soft magnetic core is then assembled into an inductor.